AVALIAÇÃO DO CONHECIMENTO DOS PROFISSIONAIS DE ENFERMAGEM DA ATENÇÃO BÁSICA SOBRE A TRIAGEM NEONATAL - Aline Russomano de Gouvêa (2022)
In 2001, the National Neonatal Screening Program (PNTN) was created in Brazil, in the interest of performing Neonatal Screening (NT) in 100% of live births through the Foot Test (PT). In view of the various functions assigned to the nursing professional in the PNTN, it is necessary that the knowledge of the nursing professional is multiplier in the Basic Health Unit (BHU), being essential training and continuing education of these professionals on the subject. The objective of this study was to evaluate the knowledge of primary care nursing professionals about the National Neonatal Screening Program in the city of Três Lagoas-MS. A cross-sectional study was carried out with the approach of 64 nursing professionals (27 nurses, 3 nursing technicians and 1 nursing assistant from the UBS in Três Lagos-MS). An Integrative Literature Review was carried out on the “Role of the Nursing Professional in the PNTN: an integrative review” whose guiding question was: What is the role of the nursing professional in the National Neonatal Screening Program? 100 were identified, and after selection, eight productions. Three categories of average emerged: (I) Technical errors in the analysis of sample collection; (II) Devaluation of the exam by professionals; (III) Lack of technical-scientific knowledge of nursing professionals. Subsequently, there was the article entitled “Knowledge of Primary Care Nursing Professionals about NT” through semi-structured educational means designed to be used for educational actions. The data showed that more than half of the nursing professionals, 59.7%, had NBT as a source of information; 34.9% consider that they have good knowledge of the TP technique; 81.8% of nurses on sending without TTP; 90 important.5% do not have information about special collections; 81.5% of nurses know about the purpose of the PNTN; 66.7% of nursing professionals know the appropriate guidance to the country of the PT refusal. The study is one of the first in the state of Mato Grosso do Sul to demonstrate the knowledge of nursing professionals regarding the PNTN. It was noted the need for new pedagogical teaching strategies in nursing to deepen the theme in the training process of these professionals. Nursing professionals must perform preventive measures to achieve the most important goal, which is morbidity and mortality.